L’accueil critique de Jules Verne en Hongrie, 1945–1989 - Kiss, Ádám László (Verbum – Analecta Neolatina, 2024)
The works of Jules Verne have been incredibly popular among Hungarian readers since their first publications in translation in the 1860s. Despite (or due to) this popularity, Hungarian literary criticism did not show any particular interest in his works apart from some sporadic essays published in the 1930s. Following World War II, from the late 1940s, the communist-socialist cultural politics excluded the authors of Western (i.e. capitalist) countries from Hungary, however, the novels of Verne started to be published again from 1952, reaching 2.5 million copies by 1969. This abundance of texts published led to more extensive, still not too numerous critical responses. In this paper, we examine the critical reception of Verne in Hungary during the period from 1945 to 1989 through articles and essays published in the daily press, journals, magazines and volumes.